2*x-267=133 287+120-x=300 300-78:x=287 750+10*х=750

2*x-267=133 287+(120-x)=300 300-78:x=287 750+10*х=750

  • 2*x-267=133                               300-78:x=287

    2*х=133+267                               78:х=300-287

    2*х=400                                      78:х=13

    х=400:2                                      х=78:13

    х=200                                        х=6

     

    287+(120-x)=300                       750+10*х=750

     120-x=300-287                         10*х=750-750 

    120-х=13                                   10*х=0

    х=120-13                                    х=0:10

    х=107                                        х=0

Добавить комментарий

Ваш e-mail не будет опубликован. Обязательные поля помечены *